2009
DOI: 10.1039/b907567d
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of transcription by platinum antitumor compounds

Abstract: Cisplatin, carboplatin, and oxaliplatin are three FDA-approved members of the platinum anticancer drug family. These compounds induce apoptosis in tumor cells by binding to nuclear DNA, forming a variety of structural adducts and triggering cellular responses, one of which is the inhibition of transcription. In this report we present (i) a detailed review of the structural investigations of various Pt-DNA adducts and the effects of these lesions on global DNA geometry; (ii) research detailing inhibition of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
365
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(374 citation statements)
references
References 144 publications
(258 reference statements)
4
365
0
5
Order By: Relevance
“…cDDP cytotoxicity is thought to be mediated in part by the conjugation of the cDDP platinum moiety to nuclear DNA, leading to intrastrand DNA cross-linking followed by cellular apoptosis (15). One possible mechanism of resistance could be that undepleted MNT-1 melanoma cells have a more rapid rate of DNA repair compared with depleted cells.…”
Section: Depletion Of Vps33a or Cno Resulted In Increased Melanoma Cellmentioning
confidence: 99%
“…cDDP cytotoxicity is thought to be mediated in part by the conjugation of the cDDP platinum moiety to nuclear DNA, leading to intrastrand DNA cross-linking followed by cellular apoptosis (15). One possible mechanism of resistance could be that undepleted MNT-1 melanoma cells have a more rapid rate of DNA repair compared with depleted cells.…”
Section: Depletion Of Vps33a or Cno Resulted In Increased Melanoma Cellmentioning
confidence: 99%
“…Upon administration of satraplatin, a number of metabolites (JM118, JM383, JM518, JM559 and JM149) are formed [43]. Satraplatin and other platinum-based compounds exhibit anti-tumour activity via the formation of DNA crosslinks in vitro [44] which in turn results in specific cellular responses, namely, apoptosis and inhibition of transcription leading to arrest of cell replication [45][46][47]. It has been amply demonstrated that the primary mechanism of cell death induced by platinum compounds is through the formation of DNA adducts [45,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…57,58 The helix of DNA being greatly distorted with the covalent binding of cisplatin, 51,52 we speculate that such binding may shorten the distance of C5′-H or even C3′-H to the guanine radical and make H abstraction more feasible than in regular DNA, thus increasing the yields of SSB or DSB. Since at low Pt ratios, in supercoiled DNA, Pt drugs form a considerable quantity of interstrand CL between guanines in opposite strands, 28 the simultaneous formation of two guanine radicals by a single LEE could induce a DSB by a single-hit process with considerable efficiency (Figure 6c).…”
Section: Modification Of the Dsb Yield Function By Cisplatin: Breamentioning
confidence: 98%